Composition for preparing carbon fiber composite paper, carbon paper and preparation method thereof, fuel cell gas diffusion layer and fuel cell
By combining acrylonitrile copolymer as a binder with chopped carbon fibers, high-performance carbon fiber composite paper was prepared, which solved the problem of poor performance of existing carbon fiber composite papers and achieved high-performance materials suitable for fuel cell gas diffusion layers.
Patent Information
- Application Number
- CN202311420983.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-05-02
AI Technical Summary
The existing carbon fiber composite paper has poor performance in breathability, resistivity, pore size and tensile strength, making it difficult to meet the needs of gas diffusion layers for fuel cells.
Acrylonitrile copolymer is used as the binder, combined with chopped carbon fiber and dispersant, and carbon fiber composite paper is prepared by hot pressing and heat treatment to form a high-performance gas diffusion layer.
The bonding performance and carbon residual carbon ratio of carbon fiber composite paper are improved, its breathability, conductivity and tensile strength are enhanced, and the performance needs of the gas diffusion layer for fuel cells are met.
Smart Images

Figure BDA0004521079740000141 
Figure BDA0004521079740000152 
Figure FDA0004521079730000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas diffusion layers for fuel cells, and in particular to a composition for preparing carbon fiber composite paper, carbon paper and a preparation method thereof, a fuel cell gas diffusion layer and a fuel cell. Background Art
[0002] Carbon fiber composite paper is widely used in electric heating materials, electromagnetic shielding materials, antistatic materials, friction materials, electrode materials and gas diffusion layer materials due to its high porosity, good electrical and thermal conductivity, excellent mechanical strength and outstanding corrosion resistance, becoming an indispensable material in the field of science and technology.
[0003] The precursor of carbon fiber composite paper is generally composed of carbon fiber and adhesive, in which the adhesive plays the role of bonding carbon fiber and improving the mechanical properties of the preform. The precursor is treated at high temperature to obtain carbon fiber composite paper. At high temperature, the non-carbon elements in the adhesive are removed, and finally the carbon fibers overlap each other through the residual carbon of the adhesive to form a network structure. The residual carbon rate of the adhesive, the bonding strength between the adhesive and the carbon fiber, and the distribution of the adhesive and the fiber play a decisive role in the air permeability, mechanical strength and conductivity of the composite paper. Therefore, in order to meet the performance requirements of carbon fiber composite paper, the adhesive usually needs to have good bonding performance to the carbon fiber, high residual carbon rate, and easy dispersion.
[0004] Adhesives are generally liquid or solid: liquid adhesives such as phenolic resin liquid often require solvents to reduce viscosity during use to obtain good fluidity, but the use of liquid adhesives will lead to the consumption of a large amount of solvents, increase pollutant emissions, and are extremely unfriendly to the environment. In addition, the amount of liquid adhesives attached is usually difficult to control and will be unevenly distributed due to gravity; solid adhesives include powdered adhesives and fibrous adhesives, among which powdered adhesives such as phenolic resin powder are prone to agglomeration during the preparation process, resulting in poor material uniformity, while traditional fibrous adhesives such as polyvinyl alcohol fibers have a low residual carbon rate and cannot bond carbon fibers well after carbonization, resulting in the performance of carbon fiber composite paper being limited.
[0005] US6540874B1 discloses using polyvinyl alcohol fiber and soluble phenolic formaldehyde as adhesives, which are pulped together with carbon fibers and then made into paper through a papermaking machine. However, since the adhesive will dissolve or semi-dissolve in water, the content of the adhesive in the carbon fiber paper is unstable, affecting the stability of the product.
[0006] US4818448A discloses using polyamide resin powder as a binder, dispersing it with carbon fibers to form an aqueous slurry, and then preparing a preform by controlled extrusion and drainage. However, since the powdered resin is prone to agglomeration, the final performance distribution of the material is uneven.
[0007] CN101047253A discloses that acrylic fiber is used as a binder, acrylic fiber and carbon fiber are prepared into paper through a conventional wet papermaking process, and carbon fiber composite paper is obtained after curing and high-temperature treatment. However, since the residual carbon rate of acrylic fiber is low, the bonding strength between carbon fibers after carbonization is weak.
[0008] CN113564749A discloses using phenolic resin / modified polyvinyl alcohol composite fibers as adhesives, eliminating the phenolic impregnation process, and the resulting carbon fiber composite paper is uniform, high in strength and good in air permeability. However, the composite fibers are difficult to spin, the solution has poor spinnability and a low carbon residue rate.
[0009] Therefore, inventing a controllable, adherent adhesive for carbon fiber composite paper with a high residual carbon rate can not only alleviate the environmental and energy crisis, but also bring strategic significance to promoting the development of carbon fiber composite paper. Summary of the invention
[0010] The purpose of the present invention is to overcome the problems of poor air permeability, resistivity, pore size and tensile strength of carbon fiber composite paper in the prior art, and to provide a composition for preparing carbon fiber composite paper, carbon paper and its preparation method, fuel cell gas diffusion layer and fuel cell.
[0011] In order to achieve the above object, the first aspect of the present invention provides a carbon fiber composite paper composition, wherein the composition comprises: an acrylonitrile copolymer, chopped carbon fibers and a dispersant.
[0012] The second aspect of the present invention provides a method for preparing carbon paper, wherein the composition of the first aspect of the present invention is subjected to heat pressing and heat treatment to obtain the carbon paper.
[0013] The third aspect of the present invention provides a carbon paper obtained by the preparation method described in the second aspect.
[0014] A fourth aspect of the present invention provides a fuel cell gas diffusion layer, wherein the fuel cell gas diffusion layer comprises the carbon paper.
[0015] A fifth aspect of the present invention provides a fuel cell, wherein the fuel cell comprises the fuel cell gas diffusion layer.
[0016] Through the above technical scheme, the present invention provides a composition for preparing carbon fiber composite paper, carbon paper and preparation method thereof, fuel cell gas diffusion layer and fuel cell, which have the following effects:
[0017] (1) The acrylonitrile copolymer adhesive provided by the present invention is used as an adhesive for carbon fiber composite paper. The adhesive has a high carbon residue rate and still has a good bonding effect after carbonization, thereby improving the performance of the product.
[0018] (2) The carbon fiber composite paper of the present invention has a simple preparation method and can be applied to a gas diffusion layer for a fuel cell.
[0019] (3) The acrylonitrile copolymer of the present invention is used as a binder. The air permeability, resistivity, pore size and tensile strength of the carbon fiber composite paper can be regulated by the composition, size and dosage of the prepared acrylonitrile copolymer adhesive to meet the performance requirements of the gas diffusion layer for fuel cells under different environmental requirements. DETAILED DESCRIPTION
[0020] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0021] A first aspect of the present invention provides a carbon fiber composite paper composition, wherein the composition comprises: an acrylonitrile copolymer, chopped carbon fibers and a dispersant.
[0022] In the present invention, the acrylonitrile copolymer is used as a binder, and the air permeability, resistivity, pore size and tensile strength of the carbon fiber composite paper can be regulated by the composition, size and dosage of the prepared acrylonitrile copolymer adhesive to meet the performance requirements of the gas diffusion layer for fuel cells under different environmental requirements. Since the acrylonitrile copolymer adhesive has good bonding properties to carbon fibers, the adhesive can adhere well to the carbon fibers. Since the present invention contains an acrylonitrile copolymer with a high residual carbon rate, the adhesive also has a high residual carbon rate. Carbon fiber composite paper is generally prepared by conventional wet papermaking technology. The use of the adhesive of the present invention and chopped carbon fibers can bond the carbon fibers into a preform by mixed papermaking and hot pressing; in the present invention, the use of acrylonitrile copolymer as an adhesive solves the problem of low residual carbon rate of polyvinyl alcohol and its modified fiber adhesives, and at the same time, the preparation process has low emissions and is environmentally friendly.
[0023] In some specific embodiments of the present invention, based on the total amount of the composition, the content of the acrylonitrile copolymer in the composition is 4-40wt%, the content of the chopped carbon fiber is 60-95wt%, and the content of the dispersant is 0.05-1wt%. The carbon fiber composite paper prepared by the composition within this range has excellent comprehensive properties.
[0024] In some specific embodiments of the present invention, the length of the chopped carbon fibers is 1-10 mm.
[0025] In some specific embodiments of the present invention, the acrylonitrile copolymer is selected from chopped acrylonitrile copolymer fibers or acrylonitrile copolymer powder.
[0026] In some specific embodiments of the present invention, the length of the short-cut acrylonitrile copolymer fiber is 1-10 mm. The short-cut acrylonitrile copolymer fiber limited to this range can better bond with the carbon fiber.
[0027] In some specific embodiments of the present invention, the acrylonitrile copolymer fiber is prepared by wet spinning of acrylonitrile copolymer, wherein the wet spinning is selected from melt spinning, wet spinning or dry spinning.
[0028] In some specific embodiments of the present invention, the acrylonitrile copolymer powder is obtained by grinding the acrylonitrile copolymer.
[0029] In some specific embodiments of the present invention, the dispersant is selected from one or more of polyacrylamide, polyacrylic acid, polyvinyl alcohol, polyethylene oxide and cellulose. Only by using the dispersant of the present invention to disperse the copolymer and the carbon fiber can a good dispersion effect be achieved.
[0030] In some specific embodiments of the present invention, the acrylonitrile copolymer comprises a structural unit A from an acrylonitrile monomer, a structural unit B from a second monomer, and an optional structural unit C from a third monomer. The acrylonitrile copolymer is obtained by polymerizing the carbon-carbon double bonds in the monomers. The optional structural unit C from the third monomer means that the acrylonitrile copolymer is a copolymerization product of an acrylonitrile monomer and a second monomer, or a copolymerization product of an acrylonitrile monomer and a second monomer and a third monomer. The final performance of the product can be regulated by adjusting the monomer composition of the acrylonitrile copolymer to achieve the best application requirements.
[0031] In some specific embodiments of the present invention, the weight ratio of the structural unit A: structural unit B: structural unit C is 50-80: 10-50: 0-10. The acrylonitrile copolymer limited to this range can be used to adjust the air permeability, resistivity, pore size and tensile strength of the carbon fiber composite paper by the composition, size and amount of the prepared acrylonitrile copolymer adhesive to meet the performance requirements of the gas diffusion layer for fuel cells under different environmental requirements.
[0032] In some specific embodiments of the present invention, the weight average molecular weight of the acrylonitrile copolymer is 50,000-300,000 g / mol.
[0033] In some specific embodiments of the present invention, the second monomer is selected from carboxyl-containing monomers and esters thereof, monomers having an amide bond and derivatives thereof, or olefins and halides thereof; preferably, the second monomer is selected from vinyl benzoic acid, 4-butene acrylic acid, methacrylic acid, vinyl acetate, methyl vinyl benzoate, 4-butene methyl acrylate, methyl methacrylate, vinyl methyl acetate, p-vinylbenzamide, 4-butene amide, acrylamide, methacrylamide, vinyl acetate, styrene or butadiene.
[0034] In some specific embodiments of the present invention, the third monomer is a modified phenolic aldehyde containing an unsaturated double bond; preferably, the third monomer has a structure shown in formula (1),
[0035] Where n is a positive integer selected from 3 to 5, and M is Wherein, L1, L2 and L3 are each independently selected from C1-C 20 an alkylene group, a cycloalkylene group or an arylene group.
[0036] In some specific embodiments of the present invention, preferably, the third monomer is selected from allyl phenolic resin, wherein the structure of allyl phenolic resin is as follows:
[0037] Wherein n=positive integer of 3-5.
[0038] In some specific embodiments of the present invention, the carbon residue rate of the acrylonitrile copolymer is 40-80wt%. The acrylonitrile copolymer fiber adhesive with a high carbon residue rate can provide enough carbon residue to tightly bond the carbon fibers, and the stress can be continuously transmitted between the carbon fibers, thus having excellent tensile strength.
[0039] In some specific embodiments of the present invention, the glass transition temperature of the acrylonitrile copolymer is 30-50° C., and the acrylonitrile copolymer can have a better bonding effect on carbon fibers when hot-pressed at a temperature higher than the glass transition temperature.
[0040] In the present invention, the composition and structure of the acrylonitrile copolymer can be determined by nuclear magnetic resonance, infrared, GPC, elemental analysis, etc., or by preparing and feeding.
[0041] The second aspect of the present invention provides a method for preparing carbon paper, wherein the composition of the first aspect of the present invention is subjected to hot pressing and heat treatment to obtain the carbon paper. The acrylonitrile copolymer is used as an adhesive, and the adhesive can well bond carbon fibers during the wet papermaking process; it can melt and move during the hot pressing process to bond the carbon fibers point to point; after the heat treatment, the polyacrylonitrile-based resin carbon obtained by the adhesive can still effectively bond carbon fibers.
[0042] In some specific embodiments of the present invention, the hot pressing temperature is 85-150° C., the hot pressing pressure is 5-30 MPa, and the hot pressing time is 1-10 min.
[0043] In some specific embodiments of the present invention, the heat treatment temperature is 1000-2600° C., and the heat treatment time is 4-8 hours.
[0044] In some specific embodiments of the present invention, the preparation method further comprises: before the hot pressing, dispersing the composition and water together and making paper.
[0045] In some specific embodiments of the present invention, the wet papermaking process includes the following steps: adding chopped carbon fibers and an acrylonitrile copolymer binder having thermoplastic characteristics to an aqueous solution of a dispersant and stirring and mixing them evenly; then sheeting the mixed slurry into a wet paper web, and drying it to obtain a carbon fiber composite paper precursor.
[0046] In some specific embodiments of the present invention, the preparation method further comprises: before the hot pressing treatment, impregnating the preform obtained by the hot pressing with a phenolic resin solution. The strength and conductivity of the carbon fiber composite paper can be improved by impregnation with the phenolic resin solution.
[0047] In some specific embodiments of the present invention, when the preparation method includes the impregnation, the hot pressing temperature is 120-200° C., the hot pressing pressure is 5-30 MPa, and the hot pressing time is 10-60 min.
[0048] In some specific embodiments of the present invention, when the preparation method includes the impregnation, the heat treatment temperature is 1000-2600° C., and the heat treatment time is 4-8 hours.
[0049] The third aspect of the present invention provides a carbon paper obtained by the preparation method described in the second aspect.
[0050] In some specific embodiments of the present invention, the carbon paper obtained by the preparation method has the overlap points of the carbon fibers well bonded by the acrylonitrile copolymer-based resin carbon, and the gaps formed by the overlap of the carbon fibers are not occupied by the acrylonitrile copolymer-based resin carbon, and the tensile strength of the carbon paper is 30-80N / cm, and the in-plane resistivity is 2.5-6.5mΩ / cm 2 , air permeability is 1600-2800mL·mm / (cm 2 ·h·mmAq).
[0051] A fourth aspect of the present invention provides a fuel cell gas diffusion layer, wherein the fuel cell gas diffusion layer comprises the carbon paper.
[0052] A fifth aspect of the present invention provides a fuel cell, wherein the fuel cell comprises the fuel cell gas diffusion layer.
[0053] In some specific embodiments of the present invention, when the fuel and oxidant ventilation pressure is 150 kPa, the test temperature is 60°C, the humidity is 95%, and the voltage is 0.6 V, the battery power density is >1.2 W / cm 2 .
[0054] The present invention will be described in detail below through examples.
[0055] The test method for the residual carbon rate of acrylonitrile copolymer is as follows: the test is performed using a TA thermogravimetric analyzer (Q5000IR), the sample size is 1-3 mg, the purge atmosphere is nitrogen, the nitrogen flow rate is greater than 20 ml / min, the temperature range is 40-700°C, and the heating rate is 10°C / min.
[0056] The test method for the glass transition temperature of acrylonitrile copolymer is as follows: using a differential scanning calorimeter (Q20) for testing, the sample size is 1-3 mg, the purge atmosphere is nitrogen, the nitrogen flow rate is greater than 20 ml / min, the temperature range is 20-250°C, and the heating rate is 5°C / min.
[0057] Rectangular sheet copying machine (PL6-A3, Xianyang Tester Experimental Equipment Co., Ltd.).
[0058] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.
[0059] Preparation Example 1
[0060] Acrylonitrile and the second monomer methyl acrylate are sequentially injected into a polymerization kettle at a mass ratio of 65:35, and an aqueous phase precipitation polymerization reaction is carried out under the conditions of pH = 2.6 and polymerization temperature = 65°C. After termination reaction, demonification and dehydration treatment, an acrylonitrile copolymer filter cake is obtained, and the weight average molecular weight of the acrylonitrile copolymer is 112000 g / mol. After that, dimethyl sulfoxide and the acrylonitrile copolymer filter cake are dissolved at a mass ratio of 100:22, and after degassing, acrylonitrile copolymer fibers are prepared by conventional wet spinning process. The acrylonitrile copolymer fiber filaments are cut into 3±0.5mm short fibers by a cutting machine for subsequent wet paper making.
[0061] Preparation Example 2
[0062] The preparation method of acrylonitrile copolymer with thermoplastic characteristics comprises the following specific steps:
[0063] Acrylonitrile and the second monomer acrylic acid are sequentially injected into a polymerization kettle at a mass ratio of 65:35, and an aqueous phase precipitation polymerization reaction is carried out under the conditions of pH = 2.6 and polymerization temperature = 65°C. After termination reaction, demonification and dehydration treatment, an acrylonitrile copolymer filter cake is obtained, and the weight average molecular weight of the acrylonitrile copolymer is 183000 g / mol. After that, dimethyl sulfoxide and the acrylonitrile copolymer filter cake are dissolved at a mass ratio of 100:22, and after degassing, acrylonitrile copolymer fibers are prepared by conventional wet spinning process. The acrylonitrile copolymer fiber filaments are cut into 3±0.5mm short fibers by a cutting machine for subsequent wet paper making.
[0064] Preparation Example 3
[0065] The preparation method of acrylonitrile copolymer with thermoplastic characteristics is as follows: the filter cake of acrylonitrile copolymer obtained by aqueous precipitation polymerization in Example 1 is crushed by a grinder to obtain acrylonitrile copolymer powder for subsequent wet paper making, and the particle size is 5 μm.
[0066] Preparation Example 4
[0067] The preparation method of acrylonitrile copolymer with thermoplastic characteristics is as follows: the acrylonitrile copolymer filter cake obtained by aqueous precipitation polymerization in Example 2 is crushed by a grinder to obtain acrylonitrile copolymer powder for subsequent wet paper making, and the particle size is 5 μm.
[0068] Preparation Example 5
[0069] The preparation method of acrylonitrile copolymer with thermoplastic characteristics comprises the following specific steps:
[0070] Acrylonitrile and the second monomer methyl acrylate were injected into the polymerization kettle in a mass ratio of 65:35, and mixed evenly in N,N-dimethylformamide solvent by ultrasonic and magnetic stirring for several hours. Solution polymerization was carried out for 6 hours under nitrogen atmosphere and 70°C. After termination reaction, denitrification and dehydration treatment, an acrylonitrile copolymer filter cake was obtained, and the weight average molecular weight of the acrylonitrile copolymer was 76000g / mol. After that, dimethyl sulfoxide and acrylonitrile copolymer filter cake were dissolved in a mass ratio of 100:22, and acrylonitrile copolymer fibers were prepared by conventional wet spinning process after degassing. The acrylonitrile copolymer fiber filaments were cut into 3±0.5mm short fibers by a cutting machine for subsequent wet paper making.
[0071] Preparation Example 6
[0072] The preparation method of acrylonitrile copolymer with thermoplastic characteristics comprises the following specific steps:
[0073] Acrylonitrile and the second monomer acrylic acid are sequentially injected into the polymerization kettle at a mass ratio of 65:35, and are uniformly mixed by ultrasonic and magnetic stirring for several hours in N,N-dimethylformamide solvent, and solution polymerization is carried out for 6 hours at 70°C in a nitrogen atmosphere. After termination reaction, denitrification and dehydration treatment, an acrylonitrile copolymer filter cake is obtained, and the weight average molecular weight of the acrylonitrile copolymer is 153000g / mol. After that, dimethyl sulfoxide and acrylonitrile copolymer filter cake are dissolved at a mass ratio of 100:22, and acrylonitrile copolymer fibers are prepared by conventional wet spinning process after degassing. The acrylonitrile copolymer fiber filaments are cut into 3±0.5mm short fibers by a cutting machine for subsequent wet paper making.
[0074] Preparation Example 7
[0075] The preparation method of acrylonitrile copolymer with thermoplastic characteristics is as follows: the acrylonitrile copolymer filter cake obtained by aqueous precipitation polymerization in Example 5 is crushed by a grinder to obtain acrylonitrile copolymer powder for subsequent wet paper making, and the particle size is 5 μm.
[0076] Preparation Example 8
[0077] The preparation method of acrylonitrile copolymer with thermoplastic characteristics is as follows: the acrylonitrile copolymer filter cake obtained by aqueous precipitation polymerization in Example 6 is crushed by a grinder to obtain acrylonitrile copolymer powder for subsequent wet paper making, and the particle size is 5 μm.
[0078] Preparation Example 9
[0079] The preparation method of acrylonitrile copolymer with thermoplastic characteristics comprises the following specific steps:
[0080] Acrylonitrile and the second monomer vinylbenzamide are sequentially injected into the polymerization kettle at a mass ratio of 65:35, and are uniformly mixed by ultrasonic and magnetic stirring for several hours in N,N-dimethylformamide solvent, and solution polymerization is carried out for 24 hours at 60°C in a nitrogen atmosphere. After termination reaction, desing and dehydration, an acrylonitrile copolymer filter cake is obtained, and the weight average molecular weight of the acrylonitrile copolymer is 177000g / mol. After that, dimethyl sulfoxide and acrylonitrile copolymer filter cake are dissolved at a mass ratio of 100:22, and acrylonitrile copolymer fibers are prepared by conventional wet spinning process after degassing. The acrylonitrile copolymer fiber filaments are cut into 3±0.5mm short fibers by a cutting machine for subsequent wet paper making.
[0081] Preparation Example 10
[0082] A method for preparing an acrylonitrile copolymer having thermoplastic characteristics, wherein the acrylonitrile copolymer filter cake obtained by solution polymerization in Example 9 is crushed by a grinder to obtain an acrylonitrile copolymer powder for subsequent wet papermaking, wherein the acrylonitrile copolymer powder has a particle size of 5 μm, a residual carbon rate of 63%, and a glass transition temperature of 45°C.
[0083] Preparation Example 11
[0084] The preparation method of acrylonitrile copolymer with thermoplastic characteristics comprises the following specific steps:
[0085] Acrylonitrile, the second monomer vinylbenzamide and the third monomer allylphenolic resin are sequentially injected into the polymerization kettle at a mass ratio of 60:30:10, and ultrasonic and magnetic stirring are performed for several hours in N,N-dimethylformamide solvent to make them uniformly mixed, and solution polymerization is performed for 24 hours at 60°C in a nitrogen atmosphere. After termination reaction, desing and dehydration treatment, an acrylonitrile copolymer filter cake is obtained, and the weight average molecular weight of the acrylonitrile copolymer is 242000g / mol. After that, dimethyl sulfoxide and acrylonitrile copolymer filter cake are dissolved at a mass ratio of 100:22, and acrylonitrile copolymer fibers are prepared by conventional wet spinning process after degassing. The acrylonitrile copolymer fiber filaments are cut into 3±0.5mm short fibers by a cutting machine for subsequent wet paper making.
[0086] Preparation Example 12
[0087] A method for preparing an acrylonitrile copolymer having thermoplastic characteristics, wherein the acrylonitrile copolymer filter cake obtained by solution polymerization in Example 11 is crushed by a grinder to obtain an acrylonitrile copolymer powder for subsequent wet papermaking, wherein the powder has a particle size of 5 μm, a residual carbon rate of 73%, and a glass transition temperature of 40°C.
[0088] Example 1
[0089] A method for preparing carbon fiber composite paper, the specific steps are as follows:
[0090] The 3 mm acrylonitrile copolymer fiber adhesive and the 3 mm chopped carbon fiber obtained in Preparation Example 1 were added to a 0.1% polyethylene oxide aqueous solution for shear dispersion to obtain a highly dispersed fiber suspension, and the suspension was papered using a rectangular sheeter to obtain base paper, which was dried at 50°C in a flat paper sample dryer. Wherein, based on the total amount of the carbon paper, the content of the acrylonitrile copolymer was 25wt%, the content of the chopped carbon fiber was 74.5wt%, and the content of the dispersant was 0.5wt%. The obtained base paper was dried and hot-pressed at 100°C, 10MPa, and 10min to obtain a preform; then the preform was heat-treated at 2300°C under nitrogen for 8h to obtain a carbon fiber composite paper.
[0091] Example 2
[0092] The method of Example 1 was followed, except that the binder was replaced with the 3 mm acrylonitrile copolymer fiber binder obtained in Preparation Example 2.
[0093] Example 3
[0094] The method of Example 1 was followed, except that the binder was replaced by the acrylonitrile copolymer powder binder obtained in Preparation Example 3.
[0095] Example 4
[0096] The method of Example 1 was followed, except that the binder was replaced by the acrylonitrile copolymer powder binder obtained in Preparation Example 4.
[0097] Example 5
[0098] The method of Example 1 was followed, except that the binder was replaced with the 3 mm acrylonitrile copolymer fiber binder obtained in Preparation Example 5.
[0099] Example 6
[0100] The method of Example 1 was followed, except that the binder was replaced with the 3 mm acrylonitrile copolymer fiber binder obtained in Preparation Example 6.
[0101] Example 7
[0102] The method of Example 1 was followed, except that the binder was replaced by the acrylonitrile copolymer powder binder obtained in Preparation Example 7.
[0103] Example 8
[0104] The method of Example 1 was followed, except that the binder was replaced by the acrylonitrile copolymer powder binder obtained in Preparation Example 8.
[0105] Example 9
[0106] The method of Example 1 was followed, except that the binder was replaced with the 3 mm acrylonitrile copolymer fiber binder obtained in Preparation Example 9.
[0107] Example 10
[0108] The method of Example 1 was followed, except that the binder was replaced by the acrylonitrile copolymer powder binder obtained in Preparation Example 10.
[0109] Embodiment 11
[0110] The method of Example 1 was followed, except that the binder was replaced with the 3 mm acrylonitrile copolymer fiber binder obtained in Preparation Example 11.
[0111] Example 12
[0112] The method of Example 1 was followed, except that the binder was replaced by the acrylonitrile copolymer powder binder obtained in Preparation Example 12.
[0113] Comparative Example 1
[0114] The method of Example 1 is followed, except that the acrylonitrile copolymer fiber binder is replaced by polyvinyl alcohol fiber to produce carbon fiber composite paper.
[0115] The residual carbon rate and glass transition temperature of the acrylonitrile copolymer in the preparation example were tested, and the results are shown in Table 1.
[0116] Table 1
[0117]
[0118]
[0119] The tensile strength, in-plane resistivity and air permeability of the carbon fiber composite paper obtained in the test examples and comparative examples were tested; at the same time, a single fuel cell was assembled with the carbon paper (the carbon paper constituted a gas diffusion layer, and the other components were a membrane electrode and a bipolar plate), and the power density of the battery was tested at a fuel and oxidant ventilation pressure of 150 kPa, a test temperature of 60°C, a humidity of 95%, and a voltage of 0.6 V. The results are shown in Table 2.
[0120] Table 2
[0121]
[0122] It can be seen from the results of Table 1 and Table 2 that by comparing Preparation Example 8 with Comparative Example 1, it can be seen that the tensile strength in Example 8 is significantly better than that in Comparative Example 1. The reason is that the residual carbon rate of the acrylonitrile copolymer fiber adhesive of the present invention is much higher than that of the PVA fiber. When the preform undergoes carbonization and graphitization, the adhesive fiber undergoes thermal shrinkage and removes a large amount of non-carbon elements. In the end, only the residual carbon of the adhesive can bond the carbon fibers together. Therefore, the acrylonitrile copolymer fiber adhesive with a high residual carbon rate can provide sufficient residual carbon to tightly bond the carbon fibers together, and the stress can be continuously transmitted between the carbon fibers, so it has excellent tensile strength performance.
[0123] By comparing Example 8 with Comparative Example 1, it can be seen that the in-plane resistivity in Example 8 is significantly lower than that in Comparative Example 1. The reason is that the residual carbon rate of the acrylonitrile copolymer fiber adhesive of the present invention is much higher than that of the PVA fiber. During the carbonization and graphitization of the preform, the acrylonitrile copolymer fiber undergoes cyclization and cross-linking to form a network structure, which greatly improves the residual carbon rate and the degree of graphitization of the residual carbon. At the same time, the adhesive fiber produces thermal shrinkage and chemical shrinkage (shrinkage caused by cross-linking reaction) during the carbonization and graphitization process, so that the short chopped carbon fibers achieve effective point-to-point (intersection) bonding through the residual carbon. Because short-cut carbon fibers have high strength and high conductivity, the conductivity and strength of carbon paper composited with carbon fibers and resin carbon residues mainly depend on the amount of carbon residues between the carbon fibers, the graphitization degree of the carbon residues, and the effectiveness of bonding. Therefore, the use of the acrylonitrile copolymer fiber adhesive of the present invention improves the resin carbon residue rate, the graphitization degree of the carbon residues, and the effective bonding between the fibers, thereby improving the conductivity (reducing the in-plane resistivity) and strength of the carbon paper; on the other hand, since effective point-to-point bonding between short-cut carbon fibers is achieved, when the conductivity and strength of the carbon paper are improved, the porosity and gas permeability of the carbon paper do not decrease significantly, and the single cell assembled under the same conditions has a higher power density. However, PVA with a low carbon residue rate cannot provide enough carbon residues to tightly bond the carbon fibers, or even cannot form a bonding structure between the carbon fibers, so there are fewer conductive loops in the carbon paper, so the resistivity is higher and the strength is lower.
[0124] By comparing Example 9 and Example 11, it can be seen that the tensile strength of Example 11 is significantly better than that of Example 9, and the in-plane resistivity of Example 11 is significantly lower than that of Example 9. The reason is that the introduced third monomer propyl phenolic resin increases the residual carbon rate of the polyacrylonitrile copolymer, making the generated carbon fiber / resin carbon network tighter, so that the stress can be continuously transmitted between the carbon fibers, thereby having more excellent tensile strength performance and improving the electrical conductivity of the carbon paper.
[0125] It can be seen from Table 2 that the carbon paper-based single cell of the present invention has a battery power density significantly higher than that of the comparative example, and the battery power density is >1.2 W / cm 2 , the performance of the gas diffusion layer for fuel cells is better.
[0126] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A composition for preparing carbon fiber composite paper, characterized in that: The composition comprises: acrylonitrile copolymer, chopped carbon fiber and a dispersant.
2. The composition according to claim 1, wherein Based on the total amount of the composition, in the composition, the content of the acrylonitrile copolymer is 4-40wt%, the content of the chopped carbon fiber is 60-95wt%, and the content of the dispersant is 0.05-1wt%; Preferably, the length of the chopped carbon fiber is 1-10 mm; Preferably, the acrylonitrile copolymer is selected from chopped acrylonitrile copolymer fibers or acrylonitrile copolymer powder; Preferably, the length of the chopped acrylonitrile copolymer fibers is 1-10 mm; Preferably, the acrylonitrile copolymer fiber is prepared by wet spinning of acrylonitrile copolymer; Preferably, the dispersant is selected from one or more of polyacrylamide, polyacrylic acid, polyvinyl alcohol, polyethylene oxide and cellulose.
3. The composition according to claim 1 or 2, wherein The acrylonitrile copolymer comprises a structural unit A derived from an acrylonitrile monomer, a structural unit B derived from a second monomer, and optionally a structural unit C derived from a third monomer; Preferably, the weight ratio of the structural unit A: structural unit B: structural unit C is 50-80: 10-50: 0-10; Preferably, the weight average molecular weight of the acrylonitrile copolymer is 50,000-300,000 g / mol.
4. The composition according to any one of claims 1 to 3, wherein The second monomer is selected from carboxyl-containing monomers and esters thereof, monomers having amide bonds and derivatives thereof, or olefins and halides thereof; preferably, the second monomer is selected from vinyl benzoic acid, 4-butene acrylic acid, methacrylic acid, vinyl acetate, methyl vinyl benzoate, 4-butene methyl acrylate, methyl methacrylate, vinyl methyl acetate, p-vinylbenzamide, 4-butene amide, acrylamide, methacrylamide, vinyl acetate, styrene or butadiene.
5. The composition according to any one of claims 1 to 4, wherein The third monomer is a modified phenolic containing an unsaturated double bond; preferably, the third monomer has a structure shown in formula (1), Where n is a positive integer selected from 3 to 5, and M is Wherein, L1, L2 and L3 are each independently selected from C1-C 20 an alkylene group, a cycloalkylene group or an arylene group.
6. The composition according to any one of claims 1 to 5, wherein The residual carbon rate of the acrylonitrile copolymer is 40-80wt%; Preferably, the glass transition temperature of the acrylonitrile copolymer is 30-50°C.
7. A method for preparing carbon paper, characterized in that: The carbon paper is obtained by subjecting the composition according to any one of claims 1 to 6 to heat pressing and heat treatment.
8. The preparation method according to claim 7, wherein: The hot pressing temperature is 85-150°C, the hot pressing pressure is 5-30MPa, and the hot pressing time is 1-10min; Preferably, the heat treatment temperature is 1000-2600° C., and the heat treatment time is 4-8 hours.
9. The preparation method according to claim 7, wherein: The preparation method further comprises: before the hot pressing, dispersing the composition and water together and making paper; Preferably, the preparation method further comprises: before the hot pressing treatment, impregnating the preform obtained by the hot pressing with a phenolic resin solution; Preferably, when the preparation method includes the impregnation, the hot pressing temperature is 120-200°C, the hot pressing pressure is 5-30MPa, and the hot pressing time is 10-60min; Preferably, when the preparation method includes the impregnation, the heat treatment temperature is 1000-2600° C. and the heat treatment time is 4-8 h.
10. Carbon paper obtained by the preparation method according to any one of claims 7 to 9.
11. The carbon paper according to claim 10, wherein: The tensile strength of the carbon paper is 30-80N / cm, and the in-plane resistivity is 2.5-6.5mΩ / cm 2 , air permeability is 1600-2800mL·mm / (cm 2 ·h·mmAq).
12. A fuel cell gas diffusion layer, characterized in that: The fuel cell gas diffusion layer comprises the carbon paper according to claim 10 or 11.
13. A fuel cell, characterized in that: The fuel cell comprises the fuel cell gas diffusion layer according to claim 12.
14. The fuel cell according to claim 13, wherein: When the fuel and oxidant ventilation pressure is 150kPa, the test temperature is 60℃, the humidity is 95%, and the voltage is 0.6V, the battery power density is >1.2W / cm 2 .
Citation Information
Patent Citations
Acrylic fiber bonded carbon fiber paper as gas diffusion media for fuel cell
CN101047253A
Preparation method of phenolic resin / modified polyvinyl alcohol composite fiber adhesive
CN113564749A
Method for fabricating light weight carbon-bonded carbon fiber composites
US4818448A
Asphalt-grade carbon fiber paper and its process
US6540874B1